STUDI EKSPLORATIF TERHADAP OPINI LAPORAN HASIL PEMERIKSAAN ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH YANG MEMPEROLEH OPINI WAJAR DENGAN PENGECUALIAN MENGGUNAKAN CONTENT ANALYSIS (STUDI KABUPATEN/KOTA SE-PROVINSI BANTEN TAHUN 2010-2014) - Lawe Anasta; Diah Iskandar (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
The purpose of this study is to know and analyze the accounts that are excluded in the financial statements of local governments throughout the Province of Banten from 2010 to 2014 that obtain a fair opinion with the exception, as well as to know and analyze problems in the accounts that excluded those Causing local government financial statements to get a reasonable opinion with the exception. An analysis of the exceptions in the inspection reports on local government financial statements that obtain fair opinions with exceptions is made using content analysis. Content analysis method is a systematic technique in categorizing words into content / charge categories using certain coding rules. Based on the audit report data on the participant's financial statements that obtained the fair opinion with the exception, it can be concluded that the components of the balance sheet that emerged as an excluded account on the audit results report on the participant's financial statements that obtained the fair opinion with the exception were assets, in particular fixed assets. While the components of budget realization reports that often appear as excluded accounts are shopping and revenue. The most frequent shopping expenditures are operating expenditures while the income that often appears as excluded accounts is local revenue.